2011
DOI: 10.1172/jci58035
|View full text |Cite
|
Sign up to set email alerts
|

Activation of KATP channels suppresses glucose production in humans

Abstract: Increased endogenous glucose production (EGP) is a hallmark of type 2 diabetes mellitus. While there is evidence for central regulation of EGP by activation of hypothalamic ATP-sensitive potassium (K ATP ) channels in rodents, whether these central pathways contribute to regulation of EGP in humans remains to be determined. Here we present evidence for central nervous system regulation of EGP in humans that is consistent with complementary rodent studies. Oral administration of the K ATP channel activator diaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 25 publications
13
99
1
Order By: Relevance
“…Furthermore, in humans, oral diazoxide, a KATP channel activator, decreases HGP, likely via KATP channel activation in the brain, consistent with the fact that, in rodents, central blockade of the KATP channel abolishes the effect of oral diazoxide (Kishore et al, 2011). Additionally, in type 1 diabetics, 6 months of diazoxide treatment improves metabolic control independent of changes in insulin production, possibly due to the aforementioned mechanism (Radtke et al, 2010), while intranasal insulin delivery reduces HGP in healthy men (Dash et al, 2015).…”
Section: Resultssupporting
confidence: 63%
“…Furthermore, in humans, oral diazoxide, a KATP channel activator, decreases HGP, likely via KATP channel activation in the brain, consistent with the fact that, in rodents, central blockade of the KATP channel abolishes the effect of oral diazoxide (Kishore et al, 2011). Additionally, in type 1 diabetics, 6 months of diazoxide treatment improves metabolic control independent of changes in insulin production, possibly due to the aforementioned mechanism (Radtke et al, 2010), while intranasal insulin delivery reduces HGP in healthy men (Dash et al, 2015).…”
Section: Resultssupporting
confidence: 63%
“…The regulation of EGP by a central pathway in humans remains unclear. Recently human study showed that diazoxide, an oral ATP-sensitive potassium channel activator, decreased EGP in human independently of pancreatic hormone secretion (11). From the results of the present study, it is anticipated that modifications in the regional activity of the hypothalamic neurons induced by STN-DBS in humans might affect peripheral glucose metabolism via vagal efferent fibers because no change in hormones like insulin or glucagon was detected.…”
Section: Discussionmentioning
confidence: 49%
“…88,89 The first hint that the human brain contributes to the control of peripheral metabolism was provided by a study assessing the effect of a pharmacologic K ATP channel opener on endogenous glucose production. 90 Experiments in rodents had already shown that acti vation of this channel in the hypothalamus decreased hepatic gluconeogenesis. Concordantly, oral administra tion of this drug reduced endogenous glucose production in humans during a hyperinsulinaemic glucose clamp.…”
Section: Effects On Peripheral Metabolismmentioning
confidence: 99%
“…Concordantly, oral administra tion of this drug reduced endogenous glucose production in humans during a hyperinsulinaemic glucose clamp. 90 The first human study to specifically address the effects of insulin in the brain in this regard compared plasma levels of glucose and insulin before and after intranasal insulin administration in >100 healthy participants. 25 These measurements were used to make a rough estimate of peripheral insulin resistance, namely, insulin resis tance as defined by HOMA.…”
Section: Effects On Peripheral Metabolismmentioning
confidence: 99%